Apparatus for flipping the polarization state of an optical pulse between a transmitter and a receiver in quantum key distribution and method thereof - Abdul Khir , Mohd Fared; Md. Yusof, Zalhan; Saharudin, Suhairi; ., Suryadi; Mohd Zain, Mohd. Nor Zaliman; Wahiddin, Mohamed Ridza; Saari, Sahbudin (2012)
An apparatus for flipping the polarization state of an optical pulse between a transmitter and a receiver in a quantum key distribution system comprising: a passive non flipping component that preserves the polarization state of said optical pulse; a passive flipping component that rotates the polarization state of said optical pulse orthogonally; and an active optical switch that receives said optical pulse and sends said optical pulse to either the said passive non flipping component or the said passive flipping component whereby the said optical pulse upon entering said active optical switch is directed either towards the passive non flipping component where its polarization state is preserved or towards the passive flipping component where its polarization state is rotated orthogonally.